UNREGISTERED CROSS-BORDER USE OF SERVICES ON THE POLISH SECTION OF THE EXTERNAL BORDER OF THE EU AND THE LOCATION OF THE SERVICE SECTOR IN THE POLISH TRADE TURNOVER WITH ITS EASTERN NEIGHBORS - Halina Powęska (Polityki Europejskie, Finanse i Marketing)
The article aims to investigate the share of services in Poland's trade turnover with the neighbouring countries at the external border of the European Union, taking into consideration the registered and unregistered turnover, as well to identify the share of the unregistered sector in the total volume of services turnover. The statistical analysis conducted on the data shows that in the years 2010-2012 the registered exports of services from Poland to Russia, Ukraine and Belarus were several times higher than the imports of services from these countries. The value of unregistered cross-border purchases of services made by Belarusians in Poland was twenty-five times higher, by Russians seven times higher and by Ukrainians twice as high as the value of the purchases made by Polish consumers in these countries. The share of the unregistered crossborder trading in the exports of services from Poland to Belarus and to Russia was higher than in the imports, whereas in the case of Ukraine the situation was reversed: the share of the unregistered imports of services was higher than the unregistered services exports.